The Dialogue of Cultures in the Aspect of Multicultural Education (Russian Approach) - Anzhelina A. Koriakina (Educational Process: International Journal)
The article is devoted to the problem of the dialogue of cultures in multicultural education according to the Russian approach. The role of the dialogue of cultures in multicultural education is discussed. Dialogue of cultures is considered as a basis of the concept of multicultural education. The concept “multicultural education” is considered as access to education by representatives of different ethnic groups and is increasingly used in the meaning of “multi-ethnic”. Thus, the multicultural educational system must take into account the diversity of ethnic cultures, the dialogical relationship of national and universal values. It is concluded that multicultural education based on dialogue of cultures is aimed at finding a balance between ethno-cultural diversity and social ties, at preserving and promoting the diversity of ethnic and cultural values, norms, patterns and forms of activity prevailing in the society, and at transferring this heritage to younger generations.